Enhancing the Economic Teachers’ Performances through Academic Supervision and Work Culture Conduciveness: Insight from Indonesian Senior High Schools (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2019)
The present study focused on an investigative issue in which Economic teachers’ performances in Tasikmalaya should be enhanced through the implementation of academic supervision and work culture conduciveness. Grounded in quantitative paradigm, this study utilised survey as the research method. This study involved 29 Economic teachers in Tasikmalaya as the research participants collected through interview, observation, document analysis and administering questionnaires. They were analysed quantitatively by deploying t-test and f-test. The results designated that academic supervision and work culture significantly affected Economic teachers in Tasikmalaya. Besides, academic supervision and work culture dominated the influence of Economic teachers’ teaching performances.